The efficiency of electrocoagulation using aluminum electrodes in treating wastewater from a dairy industry - Valente, Gerson de Freitas Silva; Mendonça, Regina Célia Santos; Pereira, José Antônio Marques (Ciência Rural, 2015)
This research deals with the investigation of electrocoagulation (EC) treatment of wastewater from a dairy plant using aluminum electrodes. Electrolysis time, pH, current density and distance between electrodes were considered to assess the removal efficiency of chemical oxygen demand (COD), total solids (TS) and their fractions and turbidity. Samples were collected from the effluent of a dairy plant using a sampling methodology proportional to the flow. The treatments were applied according to design factorial of half fraction with two levels of treatments and 3 repetitions at the central point. The optimization of parameters for treating dairy industry effluent by electrocoagulation using aluminum electrodes showed that electric current application for 21 minutes, an initial sample pH near 5.0 and a current density of 61.6A m^-2 resulted in a significant reduction in COD by 57%; removal of turbidity by 99%, removal of total suspended solids by 92% and volatile suspended solids by 97%; and a final treated effluent pH of approximately 10. Optimum operating condition was used for cost calculations show that operating cost is approximately 3.48R$ m^-3.

Eletrodos de alumínio foram usados para o tratamento de efluente de uma indústria de laticínios por eletrocoagulação. Tempo de eletrólise, pH, densidade de corrente elétrica e distância entre eletrodos foram os parâmetros operacionais usados para avaliar a eficiência de remoção da demanda química de oxigênio (DQO), sólidos totais (ST) e suas frações e turbidez. Amostras foram coletadas usando a metodologia de amostragem composta, proporcional à vazão. Os tratamentos foram aplicados segundo um delineamento fatorial de meia fração com dois níveis e 3 repetições no ponto central. As melhores condições operacionais foram tempo de eletrólise de 21 minutos, pH inicial de aproximadamente 5,0 e densidade de corrente elétrica de 61,6A m^-2, resultando em redução de 57% de DQO, remoção de turbidez de 99%, remoção de sólidos suspensos totais de 92% e sólidos suspensos voláteis de 97%. O pH do efluente tratado foi de aproximadamente 10. Para a condição otimizada, o custo operacional foi de aproximadamente 3, 48 R$ m^-3.
Keywords: Electrolysis; Dairy industry; Electrocoagulation; Eletrólise; Indústria de laticínios; Eletrocoagulação